A STUDY ON THE USE OF SUBSTITUTION DRILL TECHNIQUE IN TEACHING GRAMMAR - Zumrah Zumrah; Konder Manurung (e-Journal of ELTS (English Language Teaching Society), 2021)
This study was conducted through Library Research Design. The objectives of this study are to analyze, describe, and explain about the implementation of substitution drill technique in teaching grammar. In this study, the data described was taken from the ones conducted within 2011-2020. There are ten studies used as the data sources in this recent study. The result of descriptive data analysis showed that the implementation of substitution drill can improve the students’ ability in English , such as the ability in conditional sentence, simple present tense, past tense, continuous tense, degrees of comparison, and the ability in using auxiliary do and does. Based on the results of the implementation of substitution drill by previous researchers, it was found that most of the students on different academic levels within 2011-2020 experienced improvement on their ability in English after the implementation of substitution drill. All the secondary data sources used different procedure but in general all drill procedure are similar using the procedure by Decanay & Donald model with the following procedure: a model, a cue, and response.